Low frequency structural dynamics of warm dense matter - Gregori, G; Gericke, DO (2009)
Measurements of the microscopic response of warm dense matter have been demonstrated by multi-keV inelastic x-ray scattering using laser-based sources. These techniques have been used to study the high frequency electron correlations (plasmons) in low to mid- Z plasmas. The advent of fourth generation light sources will provide high fluxes of narrowband and coherent x rays that will allow to look at the low frequency correlations (the ion-acoustic waves). In this paper we present an analysis of such low frequency modes by calculating the frequency dependent ion-ion structure factor. Our model includes all the relevant multibody contributions arising from strong coupling and nonideal plasma effects. In particular, the ion-ion structure factor is obtained within the memory function formalism by satisfying a finite number of sum rules. This work could be used as a basis to a direct experimental test of dense plasma model as soon as keV free electron laser sources will become available. © 2009 American Institute of Physics.